Double Free Style Perforator Propeller Flaps for Large Posterior Trunk Defects Post Sarcoma Excision - Bindu, Ameya; Ghazwan Ahmad, Quazi; Jaiswal, Dushyant; Gour, Vijayendra; Yadav, Prabha; Mathews, Saumya; Kumar, Vineet; Mantri, Mayur; Shankhdhar, Vinay Kant (Indian Journal of Plastic Surgery, 2025)
Large posterior trunk defects due to radical sarcoma excisions conventionally mandate a free flap, needing vein grafts for pedicle length and skin grafts for donor site. Conventional options like skin grafting or local (fasciocutaneous or myocutaneous) flaps are either unsuitable due to paucity of tissues or ill-advised in view of adjuvant radiotherapy. Perforator flaps are now an established option for back defects, and the use of single flap is quite common and widely reported. Larger defects can be dealt with by planning two such flaps on separate perforators.Retrospective analysis of consecutive double perforator flaps was done for indication of resection, size of defects, size of flaps, perforator origin, complications, and tolerance for radiation. Flaps were planned in freestyle manner, committed after visualization and dissection of the selected perforators through the defect, to enable best possible design for tissue recruitment and primary closure of donor sites.Twenty-four flaps were performed in 12 patients. Average defect size was 168.5 cm2. One flap was lost to an arterial issue. Two flaps had venous insufficiency that resolved with release of sutures but needed secondary suturing and second flap respectively for marginal necrosis. Three cases needed skin grafts at remnant defects and site of suture dehiscence. Postoperative radiation was tolerated well.Double perforator flaps are viable alternative to free flaps for large posterior trunk defects. The native perforator-based supply and abundant skin of the back and neighboring trunk are well utilized to this effect. Primary donor site closure keeps morbidity to minimum.
Keywords: back defects; posterior trunk defects; double perforator flaps; freestyle perforator flaps; lumbar; intercostal; paraspinal perforators